Investment Opportunity Set and Voluntary Disclosure of Prospective Information: A Simultaneous Equations Approach - Hossain, Mahmud; Ahmed, K.; Godfrey, J. (Wiley-Blackwell Publishing Ltd., 2005)
This paper examines empirically the relationship between the level of disclosure of prospective information and the investment opportunity set for firms in New Zealand. Using a systems (two-stage least squares) approach that explicitly controls for potential endogeneity between disclosure and IOS, we find that the level of prospective information disclosure is significantly and positively related to IOS in both specifications in our simultaneous analysis. Further, we document that prospective information disclosure is positively related to firm size and new security offerings, and is not related to inside ownership and firm profitability. IOS is positively impacted by a firm's investments in fixed assets and its profitability. Finally, we find that forward looking disclosure levels are positively related to the proportion of outside directors on the board and negatively related to barriers to entry, but these findings are not robust across alternative model specifications.